Blood Biochemicals of Broiler Chickens after Been Fed Cassia obtusifolia Seed Meal - Neils , J.S.; Augustine, C.; Mojaba, D.I.; Dazala, U.I. (International Journal of Poultry Science, 2013)
The effect of processed Cassia obtusifolia seed meal as a replacement of protein on blood biochemistry (protein, albumin, globulin, Creatinine and cholesterol) was studied. One hundred and twenty (120) day old broilers chicks purchased from reputable source were randomly divided into four dietary treatments in a Randomized Complete Block Design (RCBD) with three replicates of ten birds each. Four experimental feeds were compounded with processed Cassia obtusifolia seed meal as replacement for protein at concentrations of 0, 2.5, 5.0 and 7.5% inclusion. The groups are as T1, T2, T3 and T4 groups, respectively, where T1 served as control. The experimental diet was fed to the birds for a period of 8 weeks. T2 (2.5%) and T3 (5.0%) groups had normal blood biochemical parameters while T4 (7.5%) did give normal range of biochemical values except for cholesterol level (172.86mg). The increase showed a level of significance (P<0.05) when compared to the normal range (52-148mg). The increase came from the high concentration (7.5%) of seed meal in feed (T4) in that T1 which was fed the conventional feed (control) did not show any change in the level of cholesterol. However, change in the concentration of cholesterol occurred with inclusion of Cassia Obtusifolia seed meal was made at higher percentage 7.5%, T4. This means that the level of cholesterol in chickens would be increased and becomes a risk factor to those who have preference for broiler meat. However, further investigations need to be carried out on the processing methods of Cassia obtusifolia seed that could enhance inclusion of seed meal beyond 7.5% with lesser risk of cholesterol build up in birds.